UKRAINIAN FUEL AND ENERGY SECTOR: DISTINCTIVE FEATURES - Azarenkova, Olesia (Studies and Scientific Researches. Economics Edition, 2015)
The paper is devoted to the analysis of Ukrainian fuel and energy sector (FES). The number of risks that threaten the stable supply of energy sources is growing. A high proportion of the energy intensity of developing economies in conjunction with their growing GDP leads to increased competition on world primary energy markets and causes significant fluctuations in energy prices, which negatively affect the global economy. There is also an important issue for world energy - limited use of non-renewable energy resources. Considering the prospects of development of Ukrainian FES, it is important to pay attention to patterns and trends of the global and national power. We have studied the basic trends of Ukrainian FES. It is the most important sector of the economy, and therefore its reform for market economy creation, price liberalization is a very important process. The current task of the energy sector of Ukraine is to be able to consistently produce and use energy to promote economic growth and improve quality of life.